Cyber loafing and innovative work behavior as predictors of perceived job performance: a Nigerian study (2024)
Previous studies on Perceived Job Performance (PJP) have focussed almost entirely on organizational settings different from the library. Furthermore, the studies did not investigate how the pertinent variables of Cyber Loafing (CL) and Innovative Work Behavior (IWB) predict PJP of the organizational workers. This study, therefore, was designed to examine CL and IWB as predictors of PJP of the personnel of some university libraries in Nigeria. Theories of Reasoned Action and Job Performance anchored the study, while the survey design of correlational type was adopted. The study population comprised the 96 professional librarians and 95 library officers in the 12 university libraries in Ogun State, Nigeria, giving a total of 191 library personnel. Total enumeration method was used to capture the entire library personnel. The instruments used were CL (α=0.71), IWB (α=0.78), and PJP (α=0.78) scales. Data were analyzed using descriptive statistics, Pearson’s product moment correlation and Multiple regression at 0.05 level of significance. The perceived job performance of the library personnel was average; the major reasons for which they engaged in cyber loafing bothered on their professional development, while their innovative work behavior was fair. The CL (r=0.32) and IWB (r=0.21) had significant relationships with PJP. The CL and IWB jointly predicted PJP (F(2;156)=10.54; Adj.R2=0.108), accounting for 11.0% of its variance. The CL (β=0.26) and IWB (β=0.13) relatively contributed to PJP. Cyber loafing and innovative work behavior influenced library personnel’s job performance in universities in Ogun State, Nigeria. These factors should be considered for improved job performance among library personnel in universities.